BeauSiccir / Nur Fadhilah Hashim ... [et al.] - Hashim, Nur Fadhilah; Rizal, Nurul Azmiah; Jaffar, Nurul Azeymasnita; Daud, Nur Hafiyatul Syahirah; Adzha, Noor Faraha Athirah (2018)
T’Beauty is a partnership company that produce a multifunctional electronic hair brush. The business is located at Lorong 8, Bandar Baru, Pulau Kambing, 21080 Kuala Terengganu, Terengganu. T’Beauty is targeted to be number one company who produce electronic hair brush in Malaysia which is named as BeauSiccir. The company focusses on providing a good quality product for the customers because the customers’ satisfaction is our main priority. T’Beauty produce BeauSiccir with a multipurpose function for a hair care purpose.